Pelatihan Membuka Cakrawala Peluang Bisnis Era Digitalisasi pada Siswa Paket C - Riki Riki; Hazriyanto Hazriyanto; Puspita Rama Nopiana; Yuliadi Yuliadi; Rudi Yanto Batara Silalahi; Andri Hanico (Jurnal Pengabdian Masyarakat (abdira), 2022)
The current era is an era of digitization that is all based on technology and information in the hands of only using a smartphone, it can all be done to support business activities. To provide knowledge about this, the activities of devotion to the community are carried out on Students of Package C PKBM Sahabat Cendekia with the aim that they get knowledge about business opportunities in the era of digitalization. Participants in this community service activity as many as 55 participants. This method of community service uses the OMPMMP method (Field Elevation, Reviewing Problems, Preparing implementation stages, carrying out service, evaluating results and making reports and publications). The result of this devotion participants can understand business opportunities in the era of digitization such as understanding about social media audience profiles, insights about market places, active social media platforms, and understanding about the potential of business in the form of soft skills and communication and challenges in doing business in the era of digitization.